2019
DOI: 10.1002/ece3.5883
|View full text |Cite
|
Sign up to set email alerts
|

The fiddler crab, Minuca pugnax, follows Bergmann's rule

Abstract: Bergmann's rule predicts that organisms at higher latitudes are larger than ones at lower latitudes. Here, we examine the body size pattern of the Atlantic marsh fiddler crab, Minuca pugnax (formerly Uca pugnax), from salt marshes on the east coast of the United States across 12 degrees of latitude. We found that M. pugnax followed Bergmann's rule and that, on average, crab carapace width increased by 0.5 mm per degree of latitude. Minuca pugnax body size also followed the temperature–size rule with body size … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 57 publications
0
8
0
1
Order By: Relevance
“…Studies of birds and mammals have found support for both rules ( 13 , 39 , 40 ). However, among ectotherms, findings have been mixed, with studies identifying support for Cope’s rule in arthropods ( 19 , 41 ) and reptiles ( 42 ); support for Bergmann’s rule in fishes ( 10 , 43 ), arthropods ( 8 , 11 , 19 ), reptiles ( 44 ), and amphibians ( 5 , 12 ); an inverse or no support for Cope’s rule in arthropods ( 45 ) and reptiles ( 23 , 46 ); and an inverse or no support for Bergmann’s rule in arthropods ( 47 ), reptiles ( 44 ), and amphibians ( 48 , 49 ). Bergmann’s rule, originally hypothesized for endothermic vertebrates ( 50 – 52 ), describes how larger endothermic species might conserve heat better in higher latitudes with cooler temperatures due to an increased surface area to volume ratio.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies of birds and mammals have found support for both rules ( 13 , 39 , 40 ). However, among ectotherms, findings have been mixed, with studies identifying support for Cope’s rule in arthropods ( 19 , 41 ) and reptiles ( 42 ); support for Bergmann’s rule in fishes ( 10 , 43 ), arthropods ( 8 , 11 , 19 ), reptiles ( 44 ), and amphibians ( 5 , 12 ); an inverse or no support for Cope’s rule in arthropods ( 45 ) and reptiles ( 23 , 46 ); and an inverse or no support for Bergmann’s rule in arthropods ( 47 ), reptiles ( 44 ), and amphibians ( 48 , 49 ). Bergmann’s rule, originally hypothesized for endothermic vertebrates ( 50 – 52 ), describes how larger endothermic species might conserve heat better in higher latitudes with cooler temperatures due to an increased surface area to volume ratio.…”
Section: Discussionmentioning
confidence: 99%
“…While Bergmann’s rule can apply at multiple evolutionary scales ( 9 ), from an interspecific viewpoint it can be defined as an ecogeographical trend where species’ body size varies as a negative function of temperature. Originally studied in mammals, this trend has now been identified in a range of animals such as crustaceans, amphibians, and ray-finned fishes ( 8 , 10 12 ). Various explanations have been proposed for Bergmann’s rule, from heat conservation in endotherms to oxygen availability in ectotherms ( 13 , 14 ).…”
mentioning
confidence: 99%
“…S4). This does not mean size might not play a role in the wild, as PIE crabs tend to be larger than their southern counterparts (Johnson et al 2019). However, some other trait (either physical or behavioral) is generating the observed difference in burrowing ability of these 2 populations.…”
Section: Discussionmentioning
confidence: 99%
“…Para as fêmeas ovígeras considerou-se a presença de ovos no marsúpio. A fim de avaliar a relação entre o tamanho corporal máximo de talitrídeos e a latitude em diferentes regiões, isto é, se a Regra de Bergmann (Johnson et al, 2019) age sobre esta espécie, foram coletados dados da literatura a partir de estudos sobre estrutura populacional de T. topitotum, juntamente com a latitude dos locais de amostragem. Os dados do presente trabalho também foram adicionados à análise e testou-se uma possível correlação entre tamanho e latitude.…”
Section: Methodsunclassified